THE ROLE OF TRAINING AND WORK DISCIPLINE ON THE EMPLOYEE PERFORMANCE OF GENERATION Z - Ilmansyah, Evan; Pamungkas, Hendrikus Atmanda Dwi; Mahardhika, Taufan Tornado; Saryatmo, Mohammad Agung (International Journal of Application on Economics and Business, 2024)
Increasing employee performance is a challenge for companies in their efforts to develop existing human resources. An employee's performance will be influenced by several things, including job training and work discipline. This is no exception for Generation Z who are also included in the workforce. The aim of this study is to determine and analyze the role of work training and work discipline on the performance of generation Z employees. This research is research that uses literature studies or literature studies whose aim is to analyze and identify findings from several previous studies in the form of articles, journals and other scientific works. The data used in this library research research includes 20 previous research journals conducted in several countries. The research results from the analysis of 20 related journals, 19 journals showed that there was a positive and significant influence between training and work discipline on employee performance, while 1 journal showed that job training did not have a significant influence on employee performance. There are still limitations and differences in results in this research so that in the future it is hoped that researchers can examine more deeply the role of training and work discipline on employee performance by using library study methods as well as statistical analysis methods such as multiple linear regression analysis using Partial Least Square (PLS) software. or the Statistical Package for the Social Sciences (SPSS).